2011
DOI: 10.1111/j.1365-2125.2011.03957.x
|View full text |Cite
|
Sign up to set email alerts
|

The risk of coronary thrombosis with cyclo‐oxygenase‐2 inhibitors does not vary with polymorphisms in two regions of the cyclo‐oxygenase‐2 gene

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • The risk of cardiovascular events with non‐steroidal anti‐inflammatory drugs (NSAIDs) varies with individual drugs and with dosage. Little is known about other factors that can modify risk. • Polymorphisms of the COX‐2 gene conceivably could alter the risk of myocardial infarction and also the risk from NSAIDs. WHAT THIS STUDY ADDS • Two common polymorphisms of the COX‐2 gene, rs 20417 (G > C) and rs 5275 (T > C), were not associated with variation in the risk of acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…These observations prompted to investigate whether COX‐2 gene polymorphisms might correlate with this variability and with the CV risk associated with the use of these drugs. However, two polymorphisms at the 5′ and 3′‐untranslated regions of the COX‐2 gene, despite having both significant effects on reducing COX‐2 expression and, thus, should be considered “low risk” haplotype, have not been shown to be correlated with a lower risk of coronary events in patients taking COXIBs . In addition, the −765G>C polymorphism has been variably associated with the risk of MI and stroke …”
Section: Cyclooxygenase Products and Cardiovascular Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…These observations prompted to investigate whether COX‐2 gene polymorphisms might correlate with this variability and with the CV risk associated with the use of these drugs. However, two polymorphisms at the 5′ and 3′‐untranslated regions of the COX‐2 gene, despite having both significant effects on reducing COX‐2 expression and, thus, should be considered “low risk” haplotype, have not been shown to be correlated with a lower risk of coronary events in patients taking COXIBs . In addition, the −765G>C polymorphism has been variably associated with the risk of MI and stroke …”
Section: Cyclooxygenase Products and Cardiovascular Pathophysiologymentioning
confidence: 99%
“…However, two polymorphisms at the 5 and 3 -untranslated regions of the COX-2 gene, despite having both significant effects on reducing COX-2 expression 338,339 and, thus, should be considered "low risk" haplotype, have not been shown to be correlated with a lower risk of coronary events in patients taking COXIBs. 340 In addition, the −765G>C polymorphism has been variably associated with the risk of MI and stroke. 341,342 Furthermore, some studies have suggested that COX inhibitors may have pharmacological mechanisms in addition to their COX activity inhibition.…”
Section: Cyclooxygenase Inhibitorsmentioning
confidence: 99%
“…Therefore, the identification of genetic determinants associated with CAD risk has tremendous importance from a public health perspective. Recently, a number of case-control studies have suggested that -765G>C polymorphism in the PTGS2 gene is associated with the risk of CAD (Cipollone et al, 2004(Cipollone et al, , 2009Hegener et al, 2006;Lee et al, 2008;Szczeklik et al, 2008;Kohsaka et al, 2008;Huuskonen et al, 2008;Li et al, 2009;Rudock et al, 2009;Sanak et al, 2010;McGettigan et al, 2011;Ol et al, 2011).…”
Section: Introductionmentioning
confidence: 99%